2020
DOI: 10.1007/s11356-020-09648-6
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic ingestion by tadpoles of pond-breeding amphibians—first results from Central Europe (SW Poland)

Abstract: Microplastics (MPs) are one of the major threats to aquatic ecosystems. Surprisingly, our knowledge of its occurrence and its impact on the organisms that dwell in small water bodies is still scarce. The aim of this study was to investigate the occurrence and chemical composition of MPs in tadpoles of pond-breeding amphibians. In total, 201 tadpoles belonging to 5 species were collected from 8 ponds located in southwestern Poland. MPs were found in all examined sites and in all studied species. Among those tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 24 publications
(34 reference statements)
2
9
1
Order By: Relevance
“…Spectroscopy revealed that all MPs particles had an anthropogenic origin and included a majority of nylon (90%), followed by polyisoprene (6%), polyurethane (2%), and 1,2-polybutadiene (2%). This study confirmed that pond-breeding amphibians are exposed to MPs [58].…”
Section: Microplastic Studies In Mollusks and Amphibianssupporting
confidence: 84%
“…Spectroscopy revealed that all MPs particles had an anthropogenic origin and included a majority of nylon (90%), followed by polyisoprene (6%), polyurethane (2%), and 1,2-polybutadiene (2%). This study confirmed that pond-breeding amphibians are exposed to MPs [58].…”
Section: Microplastic Studies In Mollusks and Amphibianssupporting
confidence: 84%
“…The particle size ranged from 550.91 to 2355.51 µm, and a significant positive correlation between the particle length and frog size was found (Pearson's correlation; r = 0.991, p = 0.001). Presumably, larger frogs catch larger prey, which, in turn, can ingest larger particles [39]. Similarly, Jâms et al [32] found a positive relationship between the animal size and length of ingested plastic, and that body length describes over 40% of the variance in the size of the largest plastic item an animal can ingest.…”
Section: Resultsmentioning
confidence: 94%
“…Similarly, surveys of anuran habitats in China found 0.48 to 21.52 microplastics L –1 across all shapes and polymer types (Hu et al 2018), suggesting that the reduction of trematode transmission to tadpole hosts via microplastics in nature is likely to be limited. However, to date, the number of surveys that have evaluated microplastic contamination in anuran habitats is low (China: Hu et al 2018; Turkey: Karaoğlu and Gül 2020; Poland: Kolenda et al 2020), making it difficult to compare the relevance of our laboratory concentrations with those in the field.…”
Section: Discussionmentioning
confidence: 99%